Effective tax and subsidy rates on human capital in Canada - John B. Burbidge; Kirk A. Collins; James B. Davies; Lonnie Magee (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Effective tax and subsidy rates (ETRs and ESRs) on human capital investment via postsecondary education are estimated for Canada in the years 2000 and 2006. The flattening of the federal personal income tax structure in 2001 substantially reduced the tax disincentive for investment in human capital. Effective subsidy rates also declined as public spending did not keep pace with rising tuition fees. The change on the tax side was strong enough to dominate the subsidy reduction according to our main results, but disaggregation shows that this result did not hold in all cases. Results are shown for College, Master's, and PhD programs, in addition to Bachelor's degrees. They are also broken down by gender, and are shown for the 25th and 75th percentiles as well as the median. Provincial detail and 1997 results are provided in the case of Bachelor's graduates.
Keywords: 330